Complete genome sequence of Methanospirillum hungatei type strain JF1. Issue 1 (December 2016) - Gunsalus, Robert; Cook, Lauren; Crable, Bryan; Rohlin, Lars; McDonald, Erin; Mouttaki, Housna; Sieber, Jessica; Poweleit, Nicole; Zhou, Hong; Lapidus, Alla; Daligault, Hajnalka; Land, Miriam; et al.
Abstract Methanospirillum hungatei strain JF1 (DSM 864) is a methane-producing archaeon and is the type species of the genusMethanospirillum, which belongs to the familyMethanospirillaceae within the orderMethanomicrobiales . Its genome was selected for sequencing due to its ability to utilize hydrogen and carbon dioxide and/or formate as a sole source of energy. Ecologically, M. hungatei functions as the hydrogen- and/or formate-using partner with many species of syntrophic bacteria. Its morphology is distinct from other methanogens with the ability to form long chains of cells (up to 100 μm in length), which are enclosed within a sheath-like structure, and terminal cells with polar flagella. The genome ofM. hungatei strain JF1 is the first completely sequenced genome of the familyMethanospirillaceae, and it has a circular genome of 3, 544, 738 bp containing 3, 239 protein coding and 68 RNA genes. The large genome ofM. hungatei JF1 suggests the presence of unrecognized biochemical/physiological properties that likely extend to the otherMethanospirillaceae and include the ability to form the unusual sheath-like structure and to successfully interact with syntrophic bacteria.